Pemanfaatan Media Digital untuk Meningkatkan Minat Belajar PAI pada Generasi Milenial - Legi Aulia Putri; Ulva Rahmi (FKIP, Universitas Palangka Raya, 2024)
In the digital era, Islamic religious education (PAI) is faced with the challenge of attracting the learning interest of the millennial generation who are accustomed to technology. This article explores the potential of using digital media as an innovative strategy to increase interest in learning PAI in the millennial generation. This approach includes the use of mobile applications, interactive learning videos, and online platforms specifically designed to provide an engaging learning experience that suits the learning styles of the millennial generation. By understanding the characteristics of the millennial generation who tend to be responsive to technology, the application of digital media in PAI classes can create a more dynamic and relevant learning atmosphere. In addition, this article explains how the integration of digital media can stimulate discussion and active participation of students, building connections between PAI material and the daily life context of the millennial generation. The successful use of digital media to increase interest in learning PAI in the millennial generation requires an active role from educators in designing interesting content, facilitating online interactions, and continuing to apply innovation in learning approaches. Thus, this article not only discusses the positive impact of using digital media in increasing interest in learning PAI in the millennial generation, but also provides practical guidance for educators to implement it effectively in the educational environment.